2019
DOI: 10.1038/s41380-019-0351-2
|View full text |Cite|
|
Sign up to set email alerts
|

Amelioration of autism-like social deficits by targeting histone methyltransferases EHMT1/2 in Shank3-deficient mice

Abstract: Many of the genes disrupted in autism are identified as histone-modifying enzymes and chromatin remodelers, most prominently those that mediate histone methylation/demethylation. However, the role of histone methylation enzymes in the pathophysiology and treatment of autism remains unknown. To address this, we used mouse models of haploinsufficiency of the Shank3 gene (a highly penetrant monogenic autism risk factor), which exhibits prominent autism-like social deficits. We found that histone methyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
87
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 67 publications
4
87
1
Order By: Relevance
“…We thus speculate that the aversive pressure imposed by light exposure alone in LDB is insufficient to suppress the drive for social reward in Shank3 +/ΔC and BTBR mice. There is an apparent contradiction as Shank3 +/ΔC mice display social withdrawal symptoms in the social approach test 17 In the modified EPM protocols, Shank3 +/ΔC and BTBR mice displayed a significantly lower SII in the social incentive trial than the object incentive trial, suggesting that in these ASD models, the incentive to engage in an interaction with a novel object may exceed that of a social stimulus. However, the SII for WT animals did not differ between the object-and social-incentive trials, which appears in contrast to 3-chamber social preference findings in which WT animals routinely demonstrate a significant preference for the social stimulus over a novel object.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus speculate that the aversive pressure imposed by light exposure alone in LDB is insufficient to suppress the drive for social reward in Shank3 +/ΔC and BTBR mice. There is an apparent contradiction as Shank3 +/ΔC mice display social withdrawal symptoms in the social approach test 17 In the modified EPM protocols, Shank3 +/ΔC and BTBR mice displayed a significantly lower SII in the social incentive trial than the object incentive trial, suggesting that in these ASD models, the incentive to engage in an interaction with a novel object may exceed that of a social stimulus. However, the SII for WT animals did not differ between the object-and social-incentive trials, which appears in contrast to 3-chamber social preference findings in which WT animals routinely demonstrate a significant preference for the social stimulus over a novel object.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes were based on power analyses with current sample size providing a power of 0.95 for P < .05, which were similar to those reported previously. 17 Data in figures are presented as mean ± SEM. F values, degrees of freedom, and P values for all ANOVAs, as well as t values and degrees of freedom for t tests, are included within the text for all statistical analyses performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated whether the loss-offunction of CNTNAP2 or AHI1 resulted in common phenotypes of synaptic dysfunction and ASD-related behavior in mice. We performed knockdown of CNTNAP2 or AHI1 in layer 2/3 pyramidal neurons of the mouse prefrontal cortex (PFC), which has been implicated in social behavior and ASD 23,[34][35][36][37][38][39][40][41][42][43] . We found that knockdown of CNTNAP2 in layer 2/3 pyramidal neurons of the PFC reduced excitatory and inhibitory synaptic transmission presumably by decreasing the number of functional synapses, elevated inhibition/excitation (I/E) balance, impaired social interaction, and induced mild pup vocalization abnormality.…”
mentioning
confidence: 99%
“…A study in the mouse brain found that proteins interacting with Shank3 in the PFC are different from those in the hippocampus and striatum (93). PFC-speci c epigenetic modi cations of histones, such as higher dimethylation (94) and lower acetylation (95) in Shank3-Het mice with an exon 21 deletion and higher dimethylation in postmortem ASD brains (94), suggest a brain region-speci c mechanism for regulation of protein expression. Notably, the expression of Shank3 is highest in the PFC compared to other regions in the macaque brain (75), whereas Shank3 isoforms containing ANK domain are highly expressed in the upper cortical layers, hippocampus and striatum of the mouse brain (96).…”
Section: Discussionmentioning
confidence: 99%